Shift analysis of thematic structure in the Indonesian - English Translation of UIN Sunan Kalijaga Website : A graduating paper submiitted in Partial Fulfillment of the requirement for gaining bachelor Degree in English Literature - Alya Masluhil Hawa (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2023)
et,1/Mumtaz c.1